MOTIVASI, DISIPLIN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT.TRANSPORINDO AGUNG SEJAHTERA CABANG MEDAN - Ayu Trisna Lafia; Akman Daulay; Sinto Sinto (BONANZA : Jurnal Ilmiah Ekonomi, Bisnis dan Keuangan, 2023)
This study tries to find out partially and simultaneously how the influence of leadership style, work ethic, and motivation on the performance of PT employees. Transporindo Agung Sejahtera. All Personnel at PT. Transporindo Agung Sejahtera, numbering 40 people, became the study population. The data was disseminated using a saturated sample approach. Questionnaires that use the Likert scale as a measurement scale are used to obtain data. Multiple linear regression tests were used in this data analysis with the SPSS program version 22.0. This study used quantitative methodology. Research instruments are used for data collection, and statistical and quantitative methods are used for analysis to test hypotheses that have been prepared. Based on the data analysis findings, work discipline, leadership style, and motivation had a minor influence on employee performance by 46.7%, 45.7%, and 5.12%, respectively. Employee performance can be explained by independent factors (motivation, work discipline, and leadership style) of 41.1%, according to the coefficient of determination test (R2). Employees can improve their performance with work discipline and good leadership. Company goals can also be met with improved performance.